IMPLEMENTASI METODE ADDIE PADA SISTEM INFORMASI PEMBUATAN RPP 1 LEMBAR DI SMK PGRI 4 PASURUAN - Sigit Riyadi; Mohammad Khusnul Chuluq (SPIRIT, 2021)
Abstract: The form of planning is RPP, which is a plan that describes learning procedures and organizations to achieve the basic competencies set out in the content standards and described in the syllabus. In this case, almost all teachers have difficulty in making RPP and in 2019 the Ministry of Education and Culture issued a new rule regarding changing the RPP into 1 sheet so that in this study it can assist teachers in making RPP in the form of RPP. digitizing and assisting teachers in the transition from the new RPP format to 1 sheet.SMK PGRI 4 Pasuruan is one of the private schools that is developing in order to improve the quality of schools. In carrying out daily operational activities, the flow of information systems at SMK PGRI 4 Pasuruan is still not optimal because there is no database that functions as a repository and making Learning Implementation Plans (RPP). ledger in the preparation of RPP reports.The research method used is the ADDIE model, in this system development method the application has experienced considerable development because each stage has experienced a good system evaluation. The results of this study were that teachers of SMK PGRI 4 Pasuruan were helped by archiving data and making lesson plans effectively and efficiently and the curriculum development team was assisted in filing curriculum documents better able to monitor the progress of theteacher's lesson plans used.